Perlindungan Petani Terkait Kebijakan Impor Beras Persprektif Mashlahah Mursalah - Warsito; Syafruddin Syam (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Mashlahah murlah is something that is good according to reason with the aim of realizing benefit or avoiding harm for human survival. This research aims to: Find out the rice import policy in Indonesia, the impact of rice imports on farmers, find out the form of farmer protection regarding the rice import policy from a mashlahah murlah perspective. This type of research is normative juridical with a conceptual approach and statute approach. The nature of this research is descriptive analysis. The data is processed and analyzed using qualitative methods. The results of the research provide an answer, namely: The policy of importing rice on a large scale from the beginning of 2021 to 2023 and even now is not appropriate because it causes greater harm, especially for farmers. on rice imports, as well as causing a decrease in farmers' income and disrupting the ideals of food sovereignty in Indonesia, the rice import policy from the Mashlahah Murlah perspective on farmer protection actually creates legal protection which must prioritize the welfare of farmers and society, helping farmers increase their income and quality of life in order to create food sovereignty in Indonesia.